Deterioration of diabetic nephropathy via stimulating secretion of cytokines by atrial natriuretic peptide - Chenxiao Liu; Qi Li; Xiu Feng; Jian Zhu; Qian Li (BMC Endocrine Disorders, 2021)
Abstract Background Atrial natriuretic peptide (ANP) is a cardiovascular and metabolic hormone that has been identified recently as being associated with chronic kidney disease (CKD) without diabetes. Cytokines such as interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α) and adiponectin (ADP) contribute to the development of type 2 diabetes (T2DM). The aim here was to investigate the relationships of ANP with cytokine levels and clinical variables in T2DM nephropathy patients. Methods A total of 81 participants with T2DM were recruited, including 37 patients with normoalbuminuria, 23 patients with microalbuminuria and 21 patients with macroalbuminuria. Serum concentrations of ANP and cytokines were measured using enzyme-linked immunosorbent assay (ELISA) kits. The correlations between ANP and clinical variables were analyzed. Multiple linear regression and logistic regression models were constructed to test the associations between ANP and the severity and presence of albuminuria. Results The macroalbuminuria patients exhibited higher plasma levels of ANP, TNF-α, IL-6, and ADP; higher serum creatinine (Cr) and blood urea nitrogen (BUN); and longer duration of diabetes mellitus (DM) than the patients with normoalbuminuria and microalbuminuria. Plasma ANP level was significantly associated with TNF-α (r = 0.876, p < 0.001), IL-6 (r = 0.816, p < 0.001) and ADP (r = 0.772, p < 0.001), independent of the duration of DM or the BUN concentration. Conclusion ANP is higher in type 2 diabetes mellitus nephropathy subjects, especially those who have macroalbuminuria, which is associated with compensatory responses to inflammation.